Association of Malassezia furfur with Onychomycosis patients In Baghdad, Iraq - Ammari, Abbas M; Talib, Noor Their; Hussein, Anaam Fuad; Abdul-Rahman, Eman Sabbah (Diyala Journal of Medicine, 2018)
Background:Onychomycosis is a fungal nail infection. It infected about 10 % of the adults. The prevalence of onychomycosis is around 5% of fungal infections. Malassezia furfur is a basidiomycetous yeast and a part of normal human skin flora. By using biochemical, immunological and molecular methods on Malassezia yeast, this genus comprises 14 species. The higher detection rate of Malassezia furfur was observed by using molecular identification methods, the internal transcribed spacer (ITS) and large subunit (LSU) regions. Objective: To detect of Malassezia furfur associated with Onychomycosis and evaluate the application of molecular method as rapid identification of Malassezia furfur. Patients and Methods:Fifty samples have been collected from patients presented signs of onychomycosis in Al- Imammian Al-Kadhamain Teaching Hospital, Baghdad, Iraq for a period of six months (from 1st of October to the 30rd of April). Clinical diagnosis was done by consultant dermatologist. Twenty nine were males and twenty one were females, the mean age of studied group was (26.12 ± 9.89) years old, with age ranging from 10 to 60 years old. Fifty healthy volunteers as control includes nail clips, the range of ages was from 1 to 60 years old with a mean of (27.88 ± 12.03) years. Patients and control were investigated for M. furfur using phenotypic and molecular analysis. Results:Males were more infected with onychomycosis than females, with a frequency percentage (58%). According to age, the most frequent among (31-40 years old) age groups. On the basis of Polymerase chain reaction (PCR) method it was showed a positive result in 6 (12%) out of 50 onychomycosis patients and a positive result in 1 (2%) out of 50 healthy volunteers. Conclusion:From these findings, it was concluded that the males were most infected than females. PCR technique is sensitive, specific and less time consuming than cultural methods .